Idiosyncratic risks, bailout, and financial crisis: A copula approach - Wang, Daphne; Nguyen, Khoa Huu (Global Business & Finance Review (GBFR), 2015)
EconStor is a publication server for scholarly economic literature, provided as a non-commercial public service by the ZBW.